Identification and Validation of the N6-Methyladenosine RNA Methylation Regulator YTHDF1 as a Novel Prognostic Marker and Potential Target for Hepatocellular Carcinoma - Bian, Saiyan; Ni, Wenkai; Zhu, Mengqi; Song, Qianqian; Zhang, Jianping; Ni, Runzhou; Zheng, Wenjie (Frontiers in Molecular Biosciences, 2020)
Purpose: N6-methyladenosine (m6A) RNA methylation has been implicated in various malignancies. This study aimed to identify the m6A methylation regulator-based prognostic signature for hepatocellular carcinoma (HCC), as well as provide candidate targets for HCC treatment. Methods: The least absolute shrinkage and selection operator (LASSO) analyses were performed to identify a risk signature in The Cancer Genome Atlas (TCGA) datasets. The risk signature was further validated in International Cancer Genome Consortium (ICGC) and PCAWG datasets. Following transfection of shRNA targeting YTHDF1, the biological activities of HCC cells were evaluated by CCK-8, wound-healing, Transwell, flow cytometry and xenograft tumor assays, respectively. The potential mechanisms mediated by YTHDF1 were predicted by Overrepresentation enrichment analysis (ORA) / Gene set enrichment analysis (GSEA) and validated by western blotting. Results: Overexpression of m6A RNA methylation regulators were correlated with malignant clinicopathological characteristics of HCC patients. The Cox regression and LASSO analysis identified a risk signature with 5 m6A methylation regulators (KIAA1429, ZC3H13, YTHDF1, YTHDF2 and METTL3). In accordance with HCC cases in TCGA, the prognostic value of risk signature was also determined in ICGC and PCAWG datasets. Following analyzing the expression and clinical implications in TCGA and GEO, YTHDF1 was chosen for further experimental validation. Knockdown of YTHDF1 significantly inhibited the proliferation, migration, and invasion of HCC cells, as well as enhanced the apoptosis in vitro. Moreover, silencing YTHDF1 repressed the growth of xenograft tumors in vivo. Mechanism investigation indicated that YTHDF1 might promote the aggressive phenotypes by facilitating epithelia to mesenchymal transition (EMT) and activating AKT/GSK-3β/β-catenin signaling. Conclusion: The current study identified a robust risk signature consisting of m6A RNA methylation regulators for HCC prognosis. In addition, YTHDF1 was a potential molecular target for HCC treatment.